2020
DOI: 10.21037/jtd.2020.01.23
|View full text |Cite
|
Sign up to set email alerts
|

Improving patient engagement, adherence, and satisfaction in lung cancer surgery with implementation of a mobile device platform for patient reported outcomes

Abstract: Background: Active patient engagement may improve their perioperative experience and outcomes. We sought to evaluate the use of a mobile device application (App) for patient engagement and patient reported outcomes (PROs) assessment following robotic lung cancer surgery. Methods: Patients with suspected lung cancer undergoing robotic resection between January-May 2019, were offered the SeamlessMD App, which was customized to meet requirements of the thoracic enhanced recovery pathway. The App guided patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…All the studies were implemented in Europe and North America (ten of them in the United States and Canada). Of the 16 studies identified, eight had a randomized clinical trial design [ 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 ], six were observational studies [ 28 , 29 , 30 , 31 , 32 , 33 ] and two were economic evaluations [ 22 , 34 ]. Of the clinical trials, five reports [ 20 , 24 , 25 , 26 , 27 ] were randomized controlled trials with a high-quality design, whereas two [ 19 , 23 ] were research letters that communicated brief reports of data.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies were implemented in Europe and North America (ten of them in the United States and Canada). Of the 16 studies identified, eight had a randomized clinical trial design [ 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 ], six were observational studies [ 28 , 29 , 30 , 31 , 32 , 33 ] and two were economic evaluations [ 22 , 34 ]. Of the clinical trials, five reports [ 20 , 24 , 25 , 26 , 27 ] were randomized controlled trials with a high-quality design, whereas two [ 19 , 23 ] were research letters that communicated brief reports of data.…”
Section: Resultsmentioning
confidence: 99%
“…The other challenge related to the integration of PGHD relate to the patient's perspective; i.e., long-term sustainability and quality of collected information [36,37]. Familiarity, perceived complexity, and trustworthiness represent the main drivers of patient adher-ence [38].…”
Section: Discussionmentioning
confidence: 99%
“…In the medical domain, particularly in oncology setting, conversational intelligence focuses primarily on (speech-enabled) chatbots [29] to contribute to screening (i.e., iDecide [30]), improving mental health state through managing psychological distress [31][32][33] and lifestyle changes [34]. Overall, chatbots have been proven as an enabler for active patient engagement, adherence and satisfaction increase [35,36]. "The self-reporting aspect delivered with the mobile application provides benefits that might otherwise be difficult to obtain" [36]:6689.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations